The Relationship between Risk Levels of Breast Cancer and Use of Early Diagnosis and Screening Services in Healthcare Workers in Turkey - Ayla ACIKGOZ; Selda YORUK; Hulya TURKMEN; Gul ERGOR (Tehran University of Medical Sciences, 2020)
Background: This study aimed to determine the factors affecting early diagnosis and screening behaviors of healthcare workers concerning breast cancer and the breast cancer risk levels using the risk identification model and to evaluate the relationship between breast cancer risk levels and early diagnosis and screening behaviors. Methods: Overall, 466 healthcare workers from Balikesir Province, Turkey participated in this cross-sectional study. Data were collected thanks to a questionnaire prepared by the researchers. Cuzick-Tyrer model was utilized to determine breast cancer risk levels. Results: 78.1% of the healthcare workers regularly perform breast self-examination (BSE), 11.6% had clinical breast examination (CBE), 7.7% had breast ultrasound scan and 4.5% had mammography. BSE behavior increased, as education level got higher. Mammography screening behavior increased in those aged 40 yr and older and those with breast or ovarian cancer history in their family. There was not any relationship between breast cancer risk levels and early diagnosis and screening behaviors. Conclusion: Early diagnosis and screening behaviors of healthcare workers were low concerning breast cancer. Age, education level and family history are the most prominent factors affecting early diagnosis and screening behaviors of healthcare workers. Informing healthcare workers on breast cancer risk factors and screening can make positive contributions to them and the public through them.